Cytokeratin Expression Profile Study in Malignant Ovarian Tumors: A Retrospective Study in Teaching Institution - Gnanamuthu, Jeyanthi; Ranjana, S. Jenita Christina; Kannan, P (Annals of Pathology and Laboratory Medicine, 2018)
Background: Expression of cytokeratin is seen in varied ovarian tumors including primary surface epithelial tumors, Granulosa cell tumors, Sertoli – Leydig cell tumors, non dysgerminomatous germ cell tumors and metastatic carcinomas. The aim of the study is to demonstrate various patterns of cytokeratin expression in epithelial and non-epithelial malignant ovarian tumors. Methods: Materials for the present study of 39 cases of malignant ovarian tumors obtained from the patients admitted during the period of two years. For histopathological examination, 10% formalin fixed embedded representative tissue sections were studied with Haematoxylin and Eosin. Detailed microscopic examination was carried out. Application of IHC for cytokeratin expression study was carried by streptavidin – biotin complex method. The details of clinical history and relevant investigations were obtained. Results: The total number of malignant ovarian tumors studied during two year period was 39 cases. Among that, serous tumors was the most common [25 cases (64.6%)], followed by Sex cord stromal tumors [6 cases (15.3%)], metastatic tumors [4 cases (10.2%)] and Germ cell tumors [4 cases (10.2%). Cytokeratin was positive in >50% of serous epithelial cells, followed by krukenberg tumor and showed focal positivity in non-epithelial tumors. Conclusion: Evaluation for pancytokeratin (AE 1 / AE 3) in the context of ovarian tumors is useful only in specific instances including identification of epithelial differentiation in an apparently undifferentiated neoplasms and distinction of dysgerminoma from non dysgerminomatous germ cell tumors. Non dysgerminomatous germ cell tumors characteristically express cytokeratin diffusely and strongly, whereas in dysgerminoma it shows only focal and weak expression.